Development of web application for Muslim traveller with emphasis on social networking - Gunawan, Teddy Surya; Kartiwi, Mira; Che Omar, Afif Abdul Fattah (2012)
In this global world, travelling to another country is becoming a necessity, especially for a Muslim. When travelling to non-Muslim country, the unfamiliar place, situation, and condition will create several problems to uphold the Islamic principles, such as finding the mosque to pray, praying time, qibla direction or halal food. Therefore, the objective of this paper is to develop a web application to solve such problems, in which the online application will verify the user’s current location and provide the required information such as the nearest mosque, available Halal restaurants in the area, prayer time, and also suitable accommodation. First, the authors identified the needs of the Muslim traveller by accessing the religious literature and conducting interviews. Secondly, the design of the application will be optimized using UML (Unified Modelling Language) diagram. Next, Wordpress will be utilized as the front end application because of its open source, modularity, high availability, robust, secure, and reliable. Furthermore, many additional plugins can be added to enhance the features, such as social network bookmarking, Facebook page, live Facebook commenting, and Facebook connect. Online visitors with Facebook account can provide feedback and recommendation to ensure that the information provided in the website will always up to date. Informal evaluation shows the effectiveness of the proposed system. It is expected that the developed system accessible at www.imantraveller.com can be benefited to the Muslim traveller.